Avaliação da resistência à corrosão de aços carbono baixa liga usando a espectroscopia de impedância eletroquímica e ensaios de campo - Renata Braga Soares (2013)
Low alloy steels have great mechanical strength, ductility and when receive addition of certain alloying elements good resistance to atmospheric corrosion. Such steels are therefore of great technological and economic interest. This work aimed at studying the corrosion resistance of three low alloy steels with intentional addition of certain alloying elements using the electrochemical impedance spectroscopy technique and corrosion non-accelerated field tests in marine and industrial atmosphere. The mass loss tests showed that in both atmospheres mass loss for SbMo steel was higher compared to other steels. With exposure lower time it was observed that the mass loss tended to be the same value for all steels. Hence, to study the kinetics of corrosion in lower temporal dimensions, we used the technique of electrochemical impedance spectroscopy. Analyses of electrochemical impedance spectroscopy (EIS) in 0,6 mol/L NaCl solution showed that the steel that showed higher corrosion resistance was SbMo steel. On the other hand the steel that had the lower resistance corrosion was CuSb steel. In 0,10 mol/L H2SO4 solution steels with higher corrosion resistance were CuSbMo and SbMo compared to CuSb steel. Thus, it appears that the enhanced content (Al + Cr) directly influences polarization resistance. This was also evidenced by measurements of scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS).